PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA ANAK NEGERI TOUR TRAVEL CIAMIS - Siti Romlah; Komarun Zaman (Pusat Riset dan Inovasi Nasional, 2023)
In this area service is very important with many people who use it to travel far or near or just send package, in this regard, many accommodation or tour & travel service providers, ranging from small businesses to large industries. Management can increase the competitiveness of a business by maximizing service delivery. The purpose of this study was to determine and analyze : 1) the effect of service quality on costumer loyalty 2) the effect of service quality on costumer satisfaction 30 the effect of costumer satisfaction on costumer loyalty 4) the effect of service quality on costumer loyalty through costumer satisfaction. This type of research is quantitative research using questionnaires as a data collection technique. This research was conducted on the ciamis tour & travel children. The population in this study were all costumer who had used tour & travel service with a sample of 100 respondents using a purposive sampling technique. Data analysis used path analysis with the help of SPSS 22 software. The results showed 1) there was a significant effect of service quality on costumerloyalty, 2) the was a significant effect of service quality on costumer satisfaction, 3) there was a significant effect of costumer satisfaction on loyalty costumer, 4) there is a significant influence of costumer satisfaction a mediating variable of service quality on costumer loyalty